Alpine Ice‐Core Evidence of a Large Increase in Vanadium and Molybdenum Pollution in Western Europe During the 20th Century. Issue 4 (22nd February 2021) - Arienzo, Monica M.; Legrand, Michel; Preunkert, Susanne; Stohl, Andreas; Chellman, Nathan; Eckhardt, Sabine; Gleason, Kelly E.; McConnell, Joseph R.
Abstract: Pollutants emitted by industrial processes are deposited across the landscape. Ice core records from mid‐latitude glaciers located close to emission sources document the history of local‐to‐regional pollution since preindustrial times. Such records underpin attribution of pollutants to specific emission sources critical to developing abatement policies. Previous ice core studies from the Alps document the overall magnitude and timing of pollution related to nitrogen and sulfur‐derived species, as well as a few metals including lead. Here, we used subannually resolved measurements of vanadium (V) and molybdenum (Mo) in two ice cores from Col du Dome (French Alps), as well as atmospheric transport and deposition modeling, to investigate sources of pollution in the free European troposphere. The noncrustal V and Mo (ncV, ncMo) components were calculated by subtracting the crustal component from the total concentration. These ice core results showed a 32‐fold increase in ncV and a 69‐fold increase in ncMo from the preindustrial era (pre‐1860) to the industrial concentration peaks. Anthropogenic V and Mo emissions in Europe were estimated using emission factors from oil and coal consumption and atmospheric transport and deposition modeling. When comparing ice core data to estimated anthropogenic V and Mo emissions in Europe, V was found to be sourced primarily from oil combustion emissions. Conversely, coal and oil combustion estimated emissions did not agree with the measured ice core Mo concentrations, suggesting that other anthropogenic Mo sources dominated coal‐burning emissions, particularly after the 1950s. Noncoal‐burning sources of Mo may include metallurgy although emission factors are poorly known. Plain Language Summary: Industrial activities release pollutants that are transported and deposited across the landscape. Such pollutants include metals that can impact wildlife, the environment, and human health. Vanadium and molybdenum metals are essential elements for life but have possible harmful effects at high concentrations. Historical anthropogenic emissions of these two metals remain uncertain. Here, we analyzed vanadium and molybdenum in two ice cores extracted from Col du Dome, located in the French Alps. Results showed an increase in pollution‐sourced vanadium and molybdenum from the preindustrial era to the 1970s and 1980s. Anthropogenic vanadium and molybdenum deposition at the core site were estimated using previously published emission factors and consumption of fossil fuels combined with atmospheric transport and deposition modeling. When comparing ice core vanadium measurements to estimated deposition from anthropogenic emissions from oil combustion, good agreement was observed—supporting that vanadium pollution in the ice was sourced primarily from oil combustion in Europe. Conversely, prior thinking was that molybdenum emissions were dominated by coal combustion, but estimated deposition from fossil fuel emissions did not agree with the ice core data. We propose instead that the processing of molybdenum ore was an additional source of molybdenum. Key Points: Ice core chemistry shows an increasing trend after 1950 with a vanadium peak in 1982 and a molybdenum peak in 1975 Comparisons to emission estimates from European fossil fuel sources confirm vanadium deposition primarily resulted from oil burning Ice core data indicate molybdenum emissions from metallurgy were at least as large as emissions from coal burning in Europe